Induced expression of the endogenous beta interferon gene in adenovirus type 5-transformed rat fibroblasts. - Nielsch, U (1992)
Tumorigenesis is a multistep process involving both genetic and epigenetic changes resulting in altered cellular gene expression. While many phenotypic attributes of transformed cells have been described, the cellular genes responsible for these phenotypes are largely unknown. In this study, we show that the interferon-stimulated gene (ISG) ISG15 is expressed in all adenovirus type 5 (Ad5)-transformed rodent cells tested, in an E1A-dependent manner. We find that the level of ISG15 mRNA correlates with the level of the transcription factor ISGF3, which has been postulated to be the transcriptional activator of ISGs. Consistent with the activation of the interferon transduction pathway in Ad5-transformed cells, beta interferon mRNA is expressed in all but the parental untransformed cell line. The level of ISG15 mRNA in Ad5-transformed cells correlated inversely with the ability of these cells to proliferate in soft agar. This appears to have functional significance, since the phenotype of poor growth in agar could be conferred upon a cell line that grows efficiently in soft agar by using conditioned media from cells that grow poorly in soft agar. The same effect could be mimicked by applying rat interferon. We conclude that the degree of activation of the interferon signal transduction pathway explains differences in the transformation phenotypes among Ad5-transformed cell lines.